Socio-Theoretical Foundations of Educational Reforms in the New Uzbekistan - Mirzayevich, Kandov Bahodir (International Journal on Human-Computing Studies, 2023)
This article explains that improving the education system, providing high-quality educational literature, educating young people in the spirit of patriotism is one of the most important issues in the development of society. Reforms in the field of education today are no less relevant than reforms in other areas, in terms of their relevance and practical significance. In the article, the main goal of the reforms carried out in New Uzbekistan is focused on a person, his values, needs and interests, turning them into real values, the fundamental nature of the updates are analyzed socially and philosophically.